2011
DOI: 10.1111/j.1440-1843.2011.02017.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective cohort study of healthcare visits and rehospitalizations after discharge of patients with community‐acquired pneumonia

Abstract: SUMMARY AT A GLANCEThe present study documented that additional healthcare visits and rehospitalizations are common, with 34% of patients with CAP doing so within 30 days of discharge. This is mainly due to a worsening of signs or symptoms of CAP and/or comorbid conditions. These findings may have implications for discharge planning and follow-up of patients with CAP. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 28 publications
5
42
2
1
Order By: Relevance
“…In other studies investigating healthcare reconsultation following a diagnosis of CAP, reasons for reconsultation were investigator assigned and, therefore, classification of reasons for healthcare utilisation were less specific than that reported by our study. 6,13 Regardless, in keeping with our data, respiratory symptoms were the most frequently observed symptoms, and accounted for 75% of visits to primary care physicians.…”
Section: Summary Of Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…In other studies investigating healthcare reconsultation following a diagnosis of CAP, reasons for reconsultation were investigator assigned and, therefore, classification of reasons for healthcare utilisation were less specific than that reported by our study. 6,13 Regardless, in keeping with our data, respiratory symptoms were the most frequently observed symptoms, and accounted for 75% of visits to primary care physicians.…”
Section: Summary Of Resultssupporting
confidence: 61%
“…In a single-centre study conducted in Spain, Adamuz et al reported that 34% of patients discharged with CAP had an episode of healthcare reconsultation within 30 days of discharge. 13 In contrast to our study, most of these episodes were A&E visits (63%) with GP visits only representing over 52.8% of healthcare reconsultation episodes. A Dutch study using coding-derived data showed an even smaller proportion of patients (8%) requiring GP consultations in the month following discharge from hospital.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 45%
“…Studies varied in their approach to identifying index hospitalizations (Table E2). Five used prospective clinical assessment (22)(23)(24)(25)(26), two used retrospective clinical assessment (27,28), and five relied on administrative claims data (29)(30)(31)(32)(33). Studies using clinical assessment often required (1) a clinical presentation consistent with pneumonia, and (2) radiologic evidence of an infiltrate.…”
Section: Methodology Of Included Studiesmentioning
confidence: 99%
“…Studies varied in their approach to defining the cause of readmission. Five studies used retrospective clinical assessment (23,(25)(26)(27), and seven studies used administrative data (12,13,(29)(30)(31) (Table E3). …”
Section: Methodology Of Included Studiesmentioning
confidence: 99%
“…En varios trabajos se ha señalado un mayor número de hombres readmitidos, tanto en estudios generales de reingresos 2,28 como en trabajos de patologías específi-cas, tales como neumonía, enfermedad pulmonar obstructiva crónica y fallo cardíaco 12,24,34,35 , pero en otros estudios el sexo no parece relacionarse con el reingreso 32 . Se requieren estudios adicionales que permitan clarificar el papel del sexo como factor de riesgo para reingreso, y los posibles factores relacionados.…”
Section: Sexounclassified